CHARACTERISTICS OF THE PREVALENCE AND CLINICAL COURSE OF PARKINSON’S DISEASE IN THE POPULATION OF THE IVANO-FRANKIVSK REGION - Геник, С. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The results of the study of Parkinson’s disease (PD) prevalence and clinical course among different gender and age groups in Ivano-Frankivsk region population are presented in the article. It was found the decrease of PD prevalence rate in a population of Ivano-Frankivsk region compared to the world-wide and nation-wide prevalence rate (32.71 cases per 100,000 population), indicating a low level of disease diagnosis. Using clinical diagnostic criteria for brain bank of the PD British Association and unified evaluation Hoehn and Yahr scale for examination of patients with PD, it was concluded that the prevalence of disease among men and patients of the old and very old age groups is increased. It was established that the severity of the clinical manifestations of PD increases with age, especially in the group of women.